2015
DOI: 10.1149/2.1101506jes
|View full text |Cite
|
Sign up to set email alerts
|

Growth Behavior of Initial Product Layer Formed on Mg Alloy Surface Induced by Polyaniline

Abstract: The quality of the interfacial protective layer induced by polyaniline (PANI) has been claimed to play a crucial role for the enhanced corrosion protection of Mg alloy, but its growth behavior is not well understood. Here some composition, structure and growth kinetics of the protective layer formed at the PANI-emeraldine base (EB) coating/AZ91D Mg alloy interface were investigated to explore the growth mechanism. Upon immersion in 0.5 M NaCl solution, the growing interface layer under EB coating exhibited a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…This increase in OCP may be due to the formation of oxide film on the aluminum base beneath the coating with 2 wt. % PANI-SSA [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This increase in OCP may be due to the formation of oxide film on the aluminum base beneath the coating with 2 wt. % PANI-SSA [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…% PANI-SSA shifted to positive value after 1 day immersion. It means that the oxide film on the metals began to form once the solution reached the metal/coating surface [ 15 , 40 , 56 ]. Furthermore, only a uniform distribution and sufficient concentration of PANI-SSA fillers ensures the compactness of coatings and releases enough sulfonate anions (dopant) to assist the formation of passive layer [ 34 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…We emphasize that Mg(OH) 2 has unique properties which can be used in broad range of applications such as an antibacterial agent, a neutraliser of acidic water pollutants, fertilizer additive, paper preservative agent, and most importantly as a fire retardant material to incorporate in polymers to reduce the flammability [48][49][50]. Moreover, many researches have shown that nanostructured Mg(OH) 2 , such as 2D flower like Mg(OH) 2 acted as an excellent flame retardant [51][52][53].…”
Section: D Mg(oh)2 Nanosheetsmentioning
confidence: 99%
“…The curve-fitted C 1s core-level spectra consisted of three peak components with binding energies at 284.7 eV, 287.3 eV, and 289.6 eV, which are attributed to C=H, C=O, and COOH groups [34]. The XPS spectra of Mg 2s primarily exhibited one main component: MgO (at 89±0.1 eV) and perhaps some MgCO 3 present on the top surface [35]. The O 1s corelevel spectrum was dominated by the peak component with binding energy at approximately 351.8 eV, which is attributed to the oxidized species [35].…”
Section: Immersion Testing In Dmemmentioning
confidence: 99%